2021
DOI: 10.1016/j.lungcan.2021.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The identification of circulating tumour DNA using MassARRAY technology in non-small-cell lung cancer (NSCLC)

Abstract: Attaining tumour material from lung cancer patients can be challenging with limited sample availability. Therefore, non-invasive means of assessing tumour material is becoming increasingly more important. Circulating tumour DNA (ctDNA), extracted from a blood sample is appealing for the patient, and can be performed serially over the course of treatment. Materials and Methods: Here, we describe an approach for profiling the blood samples of 103 NSCLC patients for 73 variants in ctDNA across a panel of actionab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 23 publications
2
4
0
Order By: Relevance
“…However, when tissue is not available or adequate for NGS analysis, tumor-derived mutation testing in plasma serves as an alternative method. Our results demonstrated concordant results in 68% of the patients between routine diagnostic NGS analysis on the pretreatment tissue biopsy and UltraSEEK ® analysis in 66 matched baseline plasma samples, comparable to previous data [28,32]. In 23% of the patients with a known driver mutation in the tumor tissue, this variant could not be detected in the matched baseline plasma sample.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, when tissue is not available or adequate for NGS analysis, tumor-derived mutation testing in plasma serves as an alternative method. Our results demonstrated concordant results in 68% of the patients between routine diagnostic NGS analysis on the pretreatment tissue biopsy and UltraSEEK ® analysis in 66 matched baseline plasma samples, comparable to previous data [28,32]. In 23% of the patients with a known driver mutation in the tumor tissue, this variant could not be detected in the matched baseline plasma sample.…”
Section: Discussionsupporting
confidence: 86%
“…A recent comparison study showed comparable sensitivity and specificity in EGFR mutation detection between the PCR-based Cobas ® EGFR Mutation Test v2 and UltraSEEK ® Lung Panel, especially with an optimal ccfDNA input for UltraSEEK ® (≥10 ng) [27]. Furthermore, it was demonstrated previously that clinically relevant variants beyond EGFR could be identified as well [27,28], including in patients with limited oligobrain metastatic disease [29]. Within the framework of the Innovative Medicines Initiative (IMI) program CANCER-ID (http://www.cancer-id.eu, accessed on 14 June 2023), the UltraSEEK ® Lung Panel on the MassARRAY ® System to detect tumor-derived driver mutations in ccfDNA of NSCLC patients at diagnosis and at progression was evaluated, as well as its ability to quantify changes in ctDNA levels during treatment as a monitoring tool.…”
Section: Introductionmentioning
confidence: 94%
“…Also, with our study, we underlined the utility of plasma ctDNA during the treatment as prognostic factor and as complementary or exclusive source to identify targetable resistance mechanisms. Finally, liquid biopsy could play a key role also in the detection of other driver-genes such as KRAS, in NSCLC patients treated with specific TKI [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…UltraSEEK lung panel (Agena Biosciences), a commercial MassARRAY panel, was used in a 103-patient cohort, and sensitivity, specificity, and concordance rate were 62.96%, 92.11%, and 84.47%, respectively ( 56 ). Pyrosequencing was used in an early study ( 57 ), and sensitivity and specificity were 75% and 100%, respectively, resulting in a concordance rate of 97.67%.…”
Section: Resultsmentioning
confidence: 99%